EP919 Obesity and inflammation combined are risk factor for early recurrence in High Grade Serous Ovarian Cancer. (1st November 2019) - Pizarro, G; Cordova, M; Cuello, M; Kato, S; Jensen, R; Branes, J; Villarroel, A; Pinto, M; Matias, M; Bravo, ML; Ibanez, C
Abstract : Introduction/Background: Ovarian cancer is the deadliest of all gynecological cancers and high-grade serous ovarian cancer (HGSOC) is the most prevalent, aggressive type. Most of the patients are diagnoses at advances stage (III or IV). Epidemiological studies show that obesity correlates to ovarian cancer incidence, also correlate with a reduced period of overall survivor (OS). Recent studies suggest ovarian tumors are associated to chronic low-grade systemic inflammation. NLR or serum LDH had a significant impact upon OS. Our objective was determine the role of obesity and inflammation as a risk factor in a HGSOC cohort. Methodology: A retrospective registry was established that includes Chilean patients diagnosed with HGSOC. demographic and clinical data were obtained, after the signing of informed consent. Results: Demographic and clinical information was obtained from 177 patients. 147 (83%) cases were diagnoses in stage III or IV. The median for overall survivor was 49 months. Obesity and systemic inflammation showed a significant reduction in OS, but not affect Progression free survival (PFS). Normoweight patient showed no difference in OS according inflammatory status, but obese patients showed significant difference. Conclusion: Obesity as inflammation are risk factor for early recurrence in HGSOC. Our results showed a reduction in overall survival according to obesity and inflammatory status. These parameters in combination show that the risk observed by the inflammatory state depends on the BMI of patients with ovarian cancer. Disclosure: Nothing to disclose.